Introduksi Teknologi Budidaya Bawang Merah Skala Pekarangan di Kecamatan Sematang Borang Kota Palembang - Ariadi, Zepri; Karenina, Tili; Oktavianti, Ika; Karmelina, Karmelina; Wiriansyah, Andhi; Natalia, Beta (Publikasi Penelitian Terapan dan Kebijakan, 2024)
Shallots are the important horticultural commodities that contribute to inflation but the level of production is still limited. Shallot cultivation is mostly carried out on Java and its development in other regions is limited. The purpose of the introduction of shallot technology was to motivate and empower the community in utilizing yard to meet needs and increase income. The implementation of shallot introduction activities was carried out through three main stages. There were of coordination consisting of initial survey activities with internal and external stakeholders, demonstration plot for shallot cultivation on the yard of business group members, and periodic monitoring and evaluation. From the introduction of shallot cultivation in the yard, it had increased the knowledge of business group Rawa Ijo Sematang Borang members in cultivating shallots and was able to motivate business group members in understanding the importance of utilizing the yard as productive land. From per 100 polybags planted with shallots with a total seed weight of 0.565 kg, a yield of 5.83 kg was obtained. Beside that, it could also reduce family consumption expenditure and increase household income.